2012
DOI: 10.1002/ange.201107669
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 2‐Azarhodacyclobutanes by Rhodium(I)–Olefin Oxidation

Abstract: Erstaunliche Metallacyclen: Zwei Azarhodacyclobutane wurde durch Oxidation des RhI‐Olefin‐Komplexes 1 hergestellt (siehe Schema; Ts=p‐Toluolsulfonyl). Beide Isomere 2 a und 2 b wurden isoliert und durch NMR‐Spektroskopie und Massenspektrometrie charakterisiert; ihre Konfigurationen wurden in NOE‐Experimenten zweifelsfrei festgestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It is noteworthy that only complexes 14 and 15 , which have comparable geometry to complex 4 , were generated (Table 4). PhINTs oxidation of complex 1 under the same reaction conditions generated a 1:1.5 mixture of isomers 3 and 4 47. Whereas we were able to obtain complex 3 selectively using a protic solvent, under no circumstances were we ever able to obtain isomer 4 exclusively.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…It is noteworthy that only complexes 14 and 15 , which have comparable geometry to complex 4 , were generated (Table 4). PhINTs oxidation of complex 1 under the same reaction conditions generated a 1:1.5 mixture of isomers 3 and 4 47. Whereas we were able to obtain complex 3 selectively using a protic solvent, under no circumstances were we ever able to obtain isomer 4 exclusively.…”
Section: Resultsmentioning
confidence: 86%
“…Oxidation with PhINTs : Having established that H 2 O 2 oxidation proceeds with excellent selectivity, we next explored the reactions of olefin complexes 6 and 7 with PhINTs. With ethylene as the olefinic ligand, we had previously shown that two isomers, 3 and 4 , were formed in aprotic solvents, but that only 3 was formed in protic solvents 47. As such, we selected MeOD as the solvent, anticipating that the reaction would be more selective than using an aprotic solvent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations